Management of Pacemaker Implantation during COVID-19 Infection - Luigi Rivetti; Roberto Mantovan; Nadir Sitta; Ricarda Marinigh; Giuseppe Allocca; Moemen Mohammed; Fausto Pizzino; Giuseppe Nucifora (Case Reports in Cardiology)
The management of device implantation during the COVID-19 infection has not well defined yet. This is the first case of complete atrioventricular block in a symptomatic patient affected by the COVID-19 infection treated with early pacemaker implantation to minimize the risk of virus contagion.